2016
DOI: 10.1073/pnas.1612158114
|View full text |Cite
|
Sign up to set email alerts
|

Cosmc is an X-linked inflammatory bowel disease risk gene that spatially regulates gut microbiota and contributes to sex-specific risk

Abstract: Inflammatory bowel disease (IBD) results from aberrant immune stimulation against a dysbiotic mucosal but relatively preserved luminal microbiota and preferentially affects males in early onset disease. However, factors contributing to sex-specific risk and the pattern of dysbiosis are largely unexplored. Core 1 β3GalT-specific molecular chaperone (Cosmc), which encodes an X-linked chaperone important for glycocalyx formation, was recently identified as an IBD risk factor by genome-wide association study. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 44 publications
1
60
0
1
Order By: Relevance
“…Host genetics may also play an important role in digestive tract diseases. Recently, a specific host molecular chaperone, Cosmc, was shown to be associated with IBD in humans, and deletion of Cosmc in mice led to loss of gut microbiota diversity (Kudelka et al, 2016). Furthermore, the structure of the fecal microbiota is affected in patients with chronic idiopathic diarrhea, suggesting that gut homeostasis is an important feature in establishing commensal organization (Swidsinski et al, 2008).…”
Section: Biogeography Of the Gut Microbiotamentioning
confidence: 99%
“…Host genetics may also play an important role in digestive tract diseases. Recently, a specific host molecular chaperone, Cosmc, was shown to be associated with IBD in humans, and deletion of Cosmc in mice led to loss of gut microbiota diversity (Kudelka et al, 2016). Furthermore, the structure of the fecal microbiota is affected in patients with chronic idiopathic diarrhea, suggesting that gut homeostasis is an important feature in establishing commensal organization (Swidsinski et al, 2008).…”
Section: Biogeography Of the Gut Microbiotamentioning
confidence: 99%
“…The sections were blocked using 0.3% H 2 O 2 and 5% BSA. Then, sections were incubated overnight at 4°C with a specific anti-Tn IgM monoclonal antibody (5 μg/mL, CA3638, clone 12A8-C7-F5, kindly provided by Dr. Tongzhong Ju, Emory University, Atlanta, Georgia, USA) 13,20,26 followed by horseradish peroxidase-conjugated antimouse IgM antibody (Abcam, ab97230) for 1 hour at room temperature. Finally, the sections were developed with DAB reagent (ZSGB-BIO, China) and counterstained with haematoxylin.…”
Section: Immunohistochemical Staining Of Tn Antigenmentioning
confidence: 99%
“…Interestingly, the expression and activity of T‐synthase require an endoplasmic reticulum(ER)‐resident molecular chaperone named Cosmc 15, 16, 17. Knockout of either T‐synthase or Cosmc in mice causes Tn expression in vivo 18, 19, 20. Besides, in gastrointestinal tract, Tn antigen can also be elongated into core 3 O‐glycans by specific glycosyltransferase‐C3GnT 21.…”
Section: Introductionmentioning
confidence: 99%
“…The study also reported gut microbiome changes in the rodents resulting from loss of Cosmc 4 . A follow-up published earlier this year characterized functional domains of the COSMC chaperone protein 5 .…”
mentioning
confidence: 91%